Differential patterns of regional neuroadrenergic cardiovascular drive in acromegalic disease. (25th April 2013) - Seravalle, Gino; Carzaniga, Chiara; Sciortino, Giovanna; Attanasio, Roberto; Fatti, Letizia Maria; Cozzi, Renato; Montini, Marcella; Vitale, Giovanni; Brambilla, Gianmaria; Cavagnini, Francesco; Mancia, Giuseppe; Grassi, Guido; et al.
Summary It has been shown that acromegaly is characterized by an autonomic imbalance and by marked sympathoinhibition. However, there is no information available as to whether adrenergic inhibition is confined to selected vascular districts or, rather, is generalized. We examined 17 newly diagnosed active acromegalic patients without hyperprolactinaemia, pituitary hormone deficiencies, obstructive sleep apnoea and cardiac hypertrophy and 14 healthy subjects matched for age, sex and body mass index. For each subject, we collected information regarding anthropometric parameters and echocardiography, and collected plasma samples to investigate anterior pituitary function, glucose and lipid metabolism and plasma leptin levels. Beat‐to‐beat mean arterial pressure, heart rate and efferent post‐ganglionic muscle and skin sympathetic nerve traffic (MSNA and SSNA, respectively; determined by microneurography) were measured. Both MSNA and SSNA were recorded in a randomized sequence over two 30 min periods. Measurements also included evaluation of SSNA responses to emotional stimulus. In addition to significant reductions in plasma leptin levels, acromegalic patients had markedly decreased MSNA compared with the healthy controls. There were no significant differences in SSNA between the two groups, either under basal conditions or in responses to arousal stimuli. There was a significant and direct correlation between MSNA and plasma leptin levels, but not between plasma leptin and SSNA. These data provide the first evidence that the sympathetic inhibition characterizing the early phase of acromegaly is not generalized to the entire cardiovascular system.